PENGGUNAAN MODEL SPRINGATE, OHLSON, ALTMAN Z-SCORE, DAN GROVER SCORE UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA MASA PANDEMI COVID 19 (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Eka Yuni Wulandari; Maslichah Maslichah (Universitas Islam Malang, 2021)
This study to find out and analyze companies that experience financial distress and non-financial distress. The financial distress analysis in this study used four predictive models, namely Springate, Ohlson, Altman Z-Score, and Grover Score models. The sample in the study is data from manufacturing companies registered with IDX during COVID-19 pandemic precisely in the third quarter of 2020 for the nine-month period ended September 30, 2020. The analysis method used is the equation of the four financial distress prediction models. The results of the analysis using the Springate Model equation there are 45 manufacturing companies predicted to experience financial distress and 28 manufacturing companies are predicted to experience non-financial distress. The Ohlson Model Equation shows that there are 24 manufacturing companies predicted to experience financial distress and 49 manufacturing companies are predicted to experience non-financial distress. The Altman Z-Score Model Equation shows that there are 12 manufacturing companies predicted to experience financial distress, 15 manufacturing companies are predicted to experience grey areas and 46 manufacturing companies are predicted to experience non-financial distress. The Grover Score Model Equation shows that there are 8 manufacturing companies predicted to experience financial distress and there are 65 manufacturing companies predicted to experience non-financial distress. Keywords : financial distress, Springate, Ohlson, Altman Z-Score, Grover Score.